ANALISIS GAYA HIDUP DAN NILAI NILAI ISLAM TERHADAP PEMBELIAN ASURANSI SYARIAH DI KALANGAN GEN Z - Annisa Ayu Kusuma; Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze how lifestyle and Islamic values influence sharia insurance purchasing decisions among generation Z. This research shows that generation Z, who were born between 1997 and 2012, have different characteristics in making financial decisions compared to previous generations. Generation Z cares more about sustainability, ethics and transparency in their purchasing decisions. Using a quantitative approach, this research collected data from 300 randomly selected respondents in Indonesia to analyze the factors that influenced their decision in choosing sharia insurance. It is hoped that the findings of this research will provide insight into the importance of understanding religious values, sustainability and transparency in generation Z's decision making in choosing insurance products.